Development and validation of a computer program for measuring emotional awareness in German—The geLEAS (German electronic Levels of Emotional Awareness Scale) - Herpertz, Julian; Taylor, Jacob; Allen, John J. B.; Herpertz, Stephan; Opel, Nils; Richter, Maike; Subic-Wrana, Claudia; Dieris-Hirche, Jan; Lane, Richard D. (Frontiers in Psychiatry, 2023)
Introduction: Emotional awareness is the ability to identify, interpret and verbalize the emotional responses of oneself and those of others. The Levels of Emotional Awareness Scale (LEAS) is an objective performance inventory that accurately measures an individual’s emotional awareness. LEAS assessments are typically scored manually and are therefore both time consuming and cognitively demanding. This study presents a German electronic scoring program for the LEAS (geLEAS), the first non-English computerized assessment approach of the LEAS. Methods: Data were collected from a healthy German community sample (N=208). We developed a modern software for computerizing LEAS scoring, an open-source text-based emotion assessment tool called VETA (Verbal Emotion in Text Assessment). We investigated if the software would arrive at similar results as hand scoring in German and if emotional awareness would show similar associations to sociodemographic information and psychometric test results as in previous studies. Results: The most frequently used scoring method of the geLEAS shows excellent internal consistency (α= .94) and high correlations with hand scoring (r=.97, p < .001). Higher emotional awareness measured by the geLEAS is associated with female gender, older age, and higher academic achievement (all p < .001). Moreover, it is linked to the ability to identify emotions in facial expressions (p < .001) and more accurate theory of mind functioning (p < .001). Discussion: An automated method for evaluating emotional awareness greatly expands the ability to study emotional awareness in clinical care and research. This study aims to advance the use of emotional awareness as a clinical and scientific parameter.